Merkel cell polyomavirus: molecular insights into the most recently discovered human tumour virus - Stakaitytė, Gabrielė; Wood, Jennifer J; Knight, Laura M.; Abdul-Sada, Hussein; Adzahar, Noor Suhana; Nwogu, Nnenna; Macdonald, Andrew; Whitehouse, Adrian (MDPI, 2014)
A fifth of worldwide cancer cases have an infectious origin, with viral infection being the foremost. One such cancer is Merkel cell carcinoma (MCC), a rare but aggressive skin malignancy. In 2008, Merkel cell polyomavirus (MCPyV) was discovered as the causative agent of MCC. It is found clonally integrated into the majority of MCC tumours, which require MCPyV oncoproteins to survive. Since its discovery, research has begun to reveal the molecular virology of MCPyV, as well as how it induces tumourigenesis. It is thought to be a common skin commensal, found at low levels in healthy individuals. Upon loss of immunosurveillance, MCPyV reactivates, and a heavy viral load is associated with MCC pathogenesis. Although MCPyV is in many ways similar to classical oncogenic polyomaviruses, such as SV40, subtle differences are beginning to emerge. These unique features highlight the singular position MCPyV has as the only human oncogenic polyomavirus, and open up new avenues for therapies against MCC.